Pengaruh Mekanisme Good Corporate Governance Terhadap Ketepatan Waktu Penyampaian Laporan Keuangan - Tabita, Oi; Astuti, Titiek Puji; Yulianto, Yulianto (ITB AAS INDONESIA, 2023)
This research is amied to give an empirical evidence on the influence of good corporate mechanism which consist of managerial ownership, institutional ownership, and the measurement of commissioner council toward the timeliness financial report. The population of this research are property corporation and real estate that regitered in Indonesia Stock Exchange (BEI) on the period 2017-2020 by using purposive technique sampling. The data of this resarch is obtained from financial report of secondary data which consist 316 data of 79 corporations. The result of this research showed that managerial ownership and the measurement of commisioner council has possitive influence toward the timeliness of corporation financial report, but institutional ownership do not influence toward the limeliness of corporation financial report. Keywords : Timeliness, GCG, Corporation Financial Report.